Multiple tuned liquid column dampers for torsional vibration control of structures experimental investigation. - Shum, K.M (Earthquake engineering & structural dynamics.)
This paper presents an experimental investigation on the performance of multiple tuned liquid column dampers (MTLCD) for reducing torsional vibration of structures in comparison with single tuned liquid column dampers (STLCD). A large structure model simulating its torsional vibration and several STL-CDs and MTLCDs of different configurations are designed and constructed. A series of harmonically forced vibration tests are conducted to evaluate the effectiveness of MTLCDs in reducing torsional vibration of the structure and to assess the performance effects of various design parameters, which include the number of TLCD units in a MTLCD, the bandwidth of a MTLCD, the frequency tuning ratio and the moment excitation amplitude. An averaging method is also used to identify the head loss coefficients of STLCDs and MTLCDs in conjunction with the free vibration test technique. The experimental results show that the performance of a MTLCD is better than a STLCD with the same water volume in reducing the torsional vibration of structure. The performance sensitivity to frequency tuning ratio can be improved by using MTLCDs.